Раневская: фрагменты жизни / Алексей Щеглов - Щеглов Алексей Валентинович (Захаров, 1998)
Экземпляры: ИСК (20000731) / Инвентарный номер: 1036244 / Цена: / Сис.шифр: 85.334.3(2Р=Рус)6-8 / Авт.знак: Щ 33 / ГРНТИ: 18 / ББК: 85.334.3(2Р=Рус)6-8